EFEKTIFITAS IMPLEMENTASI MODEL QUANTUM LEAP DALAM MENINGKATKAN PANGSA PASAR - Suroyya Favourita (University of Merdeka Malang, 2010)
The aim of this research was to find out the difference of fund and credit market share before quantum leapmodel implementation and one year after implementation. This research had been done at the Bank X(Persero) Tbk. in region 06 Surabaya. It consists of 29 branches as population and respondents. It used thetool of t-test and ANOVA to compare fund and credit market share before and after implementation. Theresult of this research showed that fund declines after implementation. This condition was strengthened byhypothesis test result. So, it was shown that there was no significance differences between before and afterimplementation. Company ability in credit contribution improved, the change was regarded as significantbetween before and after implementation. Based on market share data result, it could be concluded that thecompany ability in getting fund decline in average, so quantum leap model was not effectively improvesfund market share. In contrary, quantum leap model effectively improves credit market share.